2021
DOI: 10.1111/ced.14786
|View full text |Cite
|
Sign up to set email alerts
|

Radiation recall dermatitis triggered by inactivated COVID‐19 vaccine

Abstract: Radiation recall dermatitis (RRD) is an acute inflammatory reaction that is localized to an area of skin previously exposed to radiation and is known to be triggered by various systemic drugs. It can be observed weeks to years after the cessation of radiotherapy, and the time interval between administration of the reaction‐triggering drug to the onset of lesions varies from minutes to days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Soyfer et al reported two cases of RRP after administration of the Pfizer-BioNTech mRNA vaccine for a SARS-CoV-2 vaccine [ 4 ]. In addition, two cases with dermatitis of RRP occurred after administration of the Sinovac vaccine of inactivated virus vaccine and AstraZeneca of vector vaccine [ 3 , 10 ]. To the best of our knowledge, this is the first report of dermatitis of RRP after administration of the mRNA-1273 SARS-CoV-2 Vaccine (manufactured by Moderna).…”
Section: Discussionmentioning
confidence: 99%
“…Soyfer et al reported two cases of RRP after administration of the Pfizer-BioNTech mRNA vaccine for a SARS-CoV-2 vaccine [ 4 ]. In addition, two cases with dermatitis of RRP occurred after administration of the Sinovac vaccine of inactivated virus vaccine and AstraZeneca of vector vaccine [ 3 , 10 ]. To the best of our knowledge, this is the first report of dermatitis of RRP after administration of the mRNA-1273 SARS-CoV-2 Vaccine (manufactured by Moderna).…”
Section: Discussionmentioning
confidence: 99%
“…Few reports of RRD after COVID‐19 vaccination have been recently published. 3 , 4 , 5 The radiation recall reactions occurred after the adenovirus vector vaccine (Oxford‐AstraZeneca, UK), 5 inactivated virus vaccine (Sinovac Coronavac, China), 3 and RNA virus vaccine (Moderna, USA). 4 Our case developed radiation recall dermatitis after injection of an inactivated virus vaccine (Sinopharm, China).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few cases of RRD have been reported after different types of COVID‐19 vaccine in the skin and lung. 3 , 4 , 5…”
Section: Introductionmentioning
confidence: 99%
“…The few available reports suggest that this vaccine can induce the radiation recall phenomenon. 1 , 2 Cole et al also reported a case of radiation recall pneumonitis after anti‐COVID vaccination. 3 In our case, nothing other than the COVID‐19 vaccine was administered after the last CT examination, so the vaccine must have been related to the onset of this case of radiation recall pneumonitis.…”
mentioning
confidence: 98%